Consideraciones en torno a la relación entre cultura y educación: a propósito de la producción y la reproducción cultural en la escuela - Solano Alpízar, José (Revista Electrónica Educare, 2001)
This article intends to articulate the notions of culture and school from the perspective of several authors and their respective theories. This academic exercise is built upon the theoretical standpoints about culture which define it as "construction of meanings in different contexts", "cultural reproduction", cultural reproductions", "cultural appropriation", "cultural capital", "variability" and "cultural compatibility". It is divided into four sections. The first one, introduces the notion of culture and its characteristics; the second one presents an overview of the main theories about reproduction from a "cultural resistance perspective"; the third one analyzes the role of cultural reproduction and cultural production from the standpoint of authors like Willis and Ogbu; the fourth and final section summarizes some views about the role of the school in looking for effective solutions to cultural differences through a "cultural compatibility" strategy.